Multi-phase flow in single fracture - Sumihiko Murata; Daisuke Fukahori; Tsuyoshi Ishida (Petrovietnam Journal, 2012)
For the successful development of a fractured reservoir, it is important to estimate the multi-phase fluid flow behavior in a single fracture. However, how the wettability of the fracture surfaces, the interfacial tension between water and oil, and the geometries of the fracture surfaces affect the multi-phase flow behavior is not understood sufficiently well.In this study, in order to understand these problems, we try to conduct a visualization experiment of water flooding ina single fracture, and then we try to simulate the multi-phase flow behavior observed in the experiment by using the lattice Boltzmann method (LBM). Consequently, we have gained a good understanding of the multi-phase flow behavior in a single fracture, and we can estimate the effect of the wettability and the interfacial tension on the multi-phase flow behavior.